Characterizing cyanobacteria from Punjab rice varieties for growth promotion - MARAG, PREMSINGSHIVSING; DHAR, DOLLY WATTAL; JAISWAL, PRANITA; TIWARI, O N; SUMAN, ARCHNA; JENA, MRUTYUNJAY JENA (The Indian Journal of Agricultural Sciences, 2021)
Cyanobacterial strains were isolated, and identified from rhizospheric soil and plant parts of rice varieties from Ludhiana, Punjab during kharif 2018. Out of the total 18 strains, 16 were heterocystous and 2 were non-hetercocystous. Seven were isolated from rice variety PB-1121 while 11 were from variety Parman-126. These belonged to four genera, Nostoc (13), Anabaena and Phormidium (2 each); and Trichormus (one).These were characterized for cell dry weight, pigments and total soluble proteins which showed a significant variation. Pigments ranged from 1.51 μg/ml to 11.63 μg/ml (chlorophyll), 0.41 μg/ml to 11.06 μg/ml (carotenoids), 1.13 μg/ml to 26.28 μg/ml (phycocyanin), 0.15 μg/ml to 33.23 μg/ml (phycoerythrin), 0.16 μg/ml to 11.18 μg/ml (allophycocyanin). Total phycobili proteins varied from a highest of 54.31 μg/ml to the lowest of 2.95 μg/ml, whereas, total soluble proteins ranged as 0.29 mg/ml to 0.70 mg/ml. Nitrogenase activity was measured as Acetylene Reduction Assay and this parameter also varied amongst the strains. Extracellular ammonia release varied as lowest of 11.10 μmole NH4 +/ml to the highest of 229.70 μmole NH4 +/ml, whereas, indole acetic acid production ranged from 7.45 μg/ml to 66.00 μg/ml.On the basis of efficient plant growth promoting parameters, these cyanobacterial strains can be studied for their possible positive influence on the performance of rice crop, which may, in turn, help in nitrogen economy after testing under pot culture and field evaluations as per required procedure and guidelines.